APAKAH KEAHLIAN KEUANGAN DIREKTUR UTAMA DAPAT MEMODERASI PENGARUH PENGUNGKAPAN PERUBAHAN IKLIM DAN KONEKSI POLITIK TERHADAP KINERJA KEUANGAN? : DOES PRESIDENT DIRECTOR’S FINANCIAL EXPERTISE MODERATE THE EFFECT OF CLIMATE CHANGE DISCLOSURE AND POLITICAL CONNECTIONS ON FINANCIAL PERFORMANCE? - Ekawati, Ekawati (Universitas Riau, 2024)
This study aims to analyze the effect of climate change disclosure and political connections on corporate financial performance with president director’s financial expertise as a moderator. Currently, climate change disclosure involves various parties, especially companies that are increasingly aware of the impact of climate change on corporate sustainability. Climate change disclosure is the process of providing information about the impacts, actions, and strategies taken by companies related to climate change. This research was conducted on food and beverage sub-sector manufacturing sector companies listed on the IDX in 2020-2022. The sample used amounted to 54 units of analysis. The data analysis technique uses moderated regression analysis (MRA).The results showed that political connections affect financial performance, but climate change disclosure has no effect on financial performance. The results also showed that president director’s was unable to moderate the effect of climate change disclosure or political connections on financial performance. The results of this study also support the resource dependency theory which states that companies will adjust to the external environment to secure resources controlled by the government. In the context of this study, political connections are considered an invisible resource that can give companies a competitive advantage.